The Doctrine of Good Faith in English Law Acceptation or Rejection: دراسة في ضوء احدث القرارات القضائية الانكليزية - علي كاظم كريم (Journal of Legal Sciences, 2020)
This article considers the doctrine of good faith in English law of contract. It analyses the different decisions of courts and the opinions of scholars and assesses whether good faith is general doctrine in English law of contract or not? It has been found that there is traditional English hostility towards a doctrine of good faith. However, in the last six years, a judicial trend, supported by some English scholars, has begun to argue that the principle of good faith should be adopted in the law of contract. This trend tries to implication contracts the duty of good faith as a implied term. The recent attempts of the Judge Leggatt and subsequent judicial decisions that have adopted his approach, although not yet reached its goal in the adoption of English law good faith as a general doctrine in contracts, but it can be said that it is likely that English law (now or later) would accept the existence of good faith in contracts, at least as an implied term in contracts.